American Delusion: Life Expectancy and Welfare in the US from an International Perspective - Rodrigo R. Soares; Rudi Rocha; Michel Szklo (Institute of Labor Economics (IZA), 2021)
Recent increases in mortality have brought life expectancy back to the forefront of the public health debate in the US. Though unprecedented, this trend comes after an equally striking phenomenon: a decades long deterioration in the relative position of the US in the world's life expectancy distribution, culminating in the late 2010s in a gap of close to 3 years to the OECD average. This paper takes a comparative approach and documents the relative performance of life expectancy in the US from an international perspective. We characterize the changes in this relative performance over time, its age and cause of death profiles, and estimate its welfare implications. We show that this phenomenon is not recent, is not restricted to very particular causes of death, but is mostly driven by adult and old age mortality. We calculate that welfare gains in the US over the last few decades could have been between 19% and 28% higher had the US been able to reproduce the average health performance of OECD countries at their typical health expenditures.
Keywords: I1; I3; O5; 330; life expectancy; health; welfare; United States